Penerapan Teknologi Varian Rasa dan Kemasan “Cassava Frozen” pada Kelompok Wanita Tani Melati - Rosada, Ida; Saida, Saida (Jurnal Pengabdian Masyarakat (ABDIRA), 2024)
This community service activity involves 1 partner, namely the Women Farmers Group (KWT) "Melati". The partner's problem is the lack of knowledge and skills. Partners don't know how to make flavor variants in frozen cassava, they can only make the original one. KWT women's lack of knowledge about good and hygienic packaging to attract consumer interest. The goal to be achieved is that it is hoped that the target community, especially KWT Melati, can apply the correct technology for flavor variants and frozen cassava packaging so that it can increase production and sales, thereby increasing the income of KWT members in particular and the community in general. The methods used in implementing this Community Service Program are counseling, training, technology demonstrations and mentoring. The results of the training on making frozen cassava with various flavors and packaging were attended by 30 members of the housewife group. Participants easily received the material because the training in making frozen cassava with various flavors and packaging technology was easy to do, the equipment used was simple, the ingredients were easy to obtain, especially cassava, which was always available, easy to apply in the household and participants were satisfied with the training provided.